2023
DOI: 10.1111/cns.14328
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture alleviates mechanical allodynia and anxiety‐like behaviors induced by chronic neuropathic pain via regulating rostral anterior cingulate cortex‐dorsal raphe nucleus neural circuit

Abstract: AimsEpidemiological studies in patients with neuropathic pain have demonstrated a strong association between neuropathic pain and psychiatric conditions such as anxiety. Preclinical and clinical work has demonstrated that electroacupuncture (EA) effectively alleviates anxiety‐like behaviors induced by chronic neuropathic pain. In this study, a potential neural circuitry underlying the therapeutic action of EA was investigated.MethodsThe effects of EA stimulation on mechanical allodynia and anxiety‐like behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 52 publications
(136 reference statements)
0
2
0
Order By: Relevance
“…Some animal studies have indicated that electroacupuncture exhibits the potential to alleviate chronic neuropathic pain-related depression or anxiety, primarily through its modulation of various molecular targets and neural circuits. 22 , 53–56 What’s more, our results showed that the RCTs and evidence-based evaluation were the current research type. By conducting rigorous RCTs and Meta-analysis, we can accurately ascertain the efficacy of acupuncture.…”
Section: Discussionmentioning
confidence: 66%
“…Some animal studies have indicated that electroacupuncture exhibits the potential to alleviate chronic neuropathic pain-related depression or anxiety, primarily through its modulation of various molecular targets and neural circuits. 22 , 53–56 What’s more, our results showed that the RCTs and evidence-based evaluation were the current research type. By conducting rigorous RCTs and Meta-analysis, we can accurately ascertain the efficacy of acupuncture.…”
Section: Discussionmentioning
confidence: 66%
“…Shen et al ( 38 ) found that electroacupuncture can treat anxiety-like behavior in Complete Freund’s Adjuvant (CFA) model rats by activating the rACC Glu-thalamus circuit without affecting pain. Xu et al ( 40 ) found that electroacupuncture can exert analgesic and anxiolytic effects on spared nerve injury (SNI) model mice by activating the rACC Glu-dorsal raphe nucleus (DRN) circuit. Hsiao et al ( 41 ) found that electroacupuncture to the Zusanli (ST36) could treat chronic inflammatory pain by inhibiting CaMKIIα signaling in the somatosensory cortex (SSC)-anterior cingulate cortex (ACC) circuit.…”
Section: Pain and Pain-related Anxietymentioning
confidence: 99%
“…Extensive research has already highlighted the positive effects of EA in alleviating symptoms associated with various neuropsychiatric conditions ( Li X. et al, 2019 ; Tamtaji et al, 2019 ; Wang et al, 2019 ). Furthermore, animal studies have demonstrated the capacity of EA to ameliorate behaviors related to anxiety, and clinical studies have confirmed its anxiolytic effects ( Amorim et al, 2022 ; Wu et al, 2022 ; Xu et al, 2023 ). Collectively, these findings suggest that EA treatment could serve as a promising complementary therapy for anxiety disorders.…”
Section: Introductionmentioning
confidence: 96%